Ambivalence and the Structure of Political Opinion
XVI, 196 p. 1 illus.
Keywords: This book represents an important step in bringing together various strands of research about attitudinal ambivalence and public opinion. Essays by a distinguished group of political scientists and social psychologists provide a conceptual framework for understanding how ambivalence is currently understood and measured, as well as its relevance to the mass public's beliefs about our political institutions and national identity. The theoretical insights, methodological innovations, and empirical analyses will add substantially to our knowledge about the nature of ambivalence in particular, and the structure and evolution of political attitudes in general.